1999
DOI: 10.1148/radiology.211.1.r99mr17203
|View full text |Cite
|
Sign up to set email alerts
|

CT Features of Systemic Lupus Erythematosus in Patients with Acute Abdominal Pain: Emphasis on Ischemic Bowel Disease

Abstract: The most common CT finding in patients with SLE and acute abdominal pain is ischemic bowel disease. CT is useful for detecting the primary cause of gastrointestinal symptoms, planning treatment, and monitoring for infarction or perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
1
13

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(112 citation statements)
references
References 29 publications
4
94
1
13
Order By: Relevance
“…Management of abdominal manifestations of SLE, in the absence of compelling radiographic or clinical findings suggestive of infarction or perforation, are steroid, antibiotics, and fluid therapy [2] . The present case reveals ischemic change of edematous, erythematous mucosa and ulcerations with normal mucosa except for lesions on flexible sigmoidoscopy [9,10] . Even though the patient has received immunosuppressive agents, he had stable disease activity during last 13 mo without using immunosuppressant or steroid and no procedure, such as colonoscopy or enema has been performed.…”
Section: Discussionmentioning
confidence: 52%
“…Management of abdominal manifestations of SLE, in the absence of compelling radiographic or clinical findings suggestive of infarction or perforation, are steroid, antibiotics, and fluid therapy [2] . The present case reveals ischemic change of edematous, erythematous mucosa and ulcerations with normal mucosa except for lesions on flexible sigmoidoscopy [9,10] . Even though the patient has received immunosuppressive agents, he had stable disease activity during last 13 mo without using immunosuppressant or steroid and no procedure, such as colonoscopy or enema has been performed.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, mesenteric angiography is not helpful for diagnosing intestinal vasculitis since typical vascular injury preferentially occurs in smaller vessels. Recent studies have shown that bowel wall thickening, a target sign, dilatation of an intestinal segment, engorgement of mesenteric vessels and increased attenuation of mesenteric fat revealed by abdominal CT scans could be key findings for the diagnosis of intestinal vasculitis (19). However, such findings can also be obtained in various cases including infectious colitis, pancreatitis and peritonitis (20).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the diagnosis of LMV is typically based on the presence of three of the following signs on abdominal computer tomography (CT): bowel wall thickening of 3 mm or more, target sign, dilatation of intestinal segments, engorgement of mesenteric vessels, and increased attenuation of mesenteric fat. 23 LMV has a propensity to affect the distribution of the superior mesenteric artery. Thus the jejunum and ileum are the most commonly affected sites, with rectal involvement being rare.…”
Section: Lupus Mesenteric Vasculitismentioning
confidence: 99%
“…Thus the jejunum and ileum are the most commonly affected sites, with rectal involvement being rare. [23][24][25] Multifocal segments of bowel involvement from multiple vascular territories occur over 90% of the time. 18,19 Inflammatory vasculitis is thought to be due to immune complex deposition, resulting in fibrinoid necrosis of subserosal vessels, leukocytoclasis on the vascular wall, and submucosal edema with diffuse mononuclear cell infiltrate.…”
Section: Lupus Mesenteric Vasculitismentioning
confidence: 99%